Respuesta :

1m1c7h

Answer:

f(x)^-1 = 1/3x - 2

Step-by-step explanation:

Replace f(x) with y and solve:

y = 3x + 6

Swap x and y

x = 3y + 6

Now isolate y

x/3 = 3y/3 + 6/3

1/3 x = y + 2

1/3 x - 2 = y + 2 - 2

y = 1/3x - 2 or f(x)^-1 = 1/3x - 2

For this case we have the following function:

[tex]f (x) = 3x + 6[/tex]

We must find the inverse of the function, then:

Replace f (x) with y:[tex]y = 3x + 6[/tex]

We exchange the variables:

[tex]x = 3y + 6[/tex]

We solve for "y":

Subtracting 6 on both sides of the equation:

[tex]x-6 = 3y[/tex]

Dividing between 3 on both sides of the equation:

[tex]y = \frac {x} {3} - \frac {6} {3}\\y = \frac {x} {3} -2[/tex]

We change y by [tex]f ^ {- 1} (x)[/tex], and finally we have:

[tex]f ^ {- 1} (x) = \frac {x} {3} -2[/tex]

ANswer:

[tex]f ^ {- 1} (x) = \frac {x} {3} -2[/tex]